1940
DOI: 10.1136/bmj.1.4133.479
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Implantation of Female and Male Hormone in Tablet Form in Women

Abstract: August 22 the uterus was curetted and the endometrium was MARCii

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1959
1959
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Loeser reported that testosterone increased women's sexual libido [7]. This observation was further supported by studies reported by Greenblatt et al.…”
Section: Testosterone Therapy In Patients With Gynecological and Sexusupporting
confidence: 70%
See 1 more Smart Citation
“…Loeser reported that testosterone increased women's sexual libido [7]. This observation was further supported by studies reported by Greenblatt et al.…”
Section: Testosterone Therapy In Patients With Gynecological and Sexusupporting
confidence: 70%
“…The notion that androgens are integral to women's sexual physiology was supported by studies demonstrating the effect of androgens on women's libido and on sexual function for the past seven decades (Figure 1). Loeser found that patients (N = 10) given implantations of testosterone tablets (smallest dose, 300 mg) experienced an enlargement of the clitoris, an increase in libido, and a heightened sense of well‐being [7]. It should be noted that 300 mg was a very high dose for pellet implantation of testosterone in a woman.…”
Section: Androgen Therapy Of Sexual Dysfunctionmentioning
confidence: 99%
“…The experimental observation that subdermal implants showed the most potent, lasting effects of any steroid formulation Parkes 1937,1938;Hamilton and Dorfman 1939) were quickly applied by clinical investigators (Vest and Howards 1939;Howards and Vest 1939;Foss 1939) and testosterone implants became an established form of androgen replacement therapy. Similar effects were observed for most biologically active steroids and their esters including androgens, estrogens and progestagens (Loeser 1940;Eidelsberg and Ornstein 1940;Emmens 1941;Forbes 1941;Biskind et al 1941;Dorfman and Hamilton 1941;Foss 1942) and very long acting depot formulations of desoxycorticosterone acetate (DOCA) lasting up to 1 year were developed for treatment of Addisons disease (Thorn and Firor 1940).…”
Section: Historymentioning
confidence: 73%
“…Shorr et al postulated that androgens not only act on the central nervous system but also at the peripheral genital level [7]. Shortly thereafter, Loeser reported that all women treated with testosterone experienced increased sexual drive, suggesting that androgens play a physiological role in enhancing libido and arousal in women [8]. These observations were further confirmed by several subsequent studies [6,9,10,11,12].…”
Section: A Historical Perspective On Androgen Therapy In Womenmentioning
confidence: 88%